1998
DOI: 10.1007/pl00005225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of imidazoline derivatives on cholinergic motility in guinea-pig ileum: involvement of presynaptic α2-adrenoceptors or imidazoline receptors?

Abstract: The present study investigates the possibility that imidazoline receptors mediate modulation of cholinergic motor functions of the guinea-pig ileum. For this purpose, the effects of a series of compounds with known affinity for alpha2-adrenoceptors and/or imidazoline recognition sites were examined on the cholinergic twitch contractions evoked by electrical field stimulation (0.1 Hz) of longitudinal muscle-myenteric plexus preparations. Additional experiments were carried out on ileal strips preincubated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…These results suggest that acotiamide may be a new orally active gastroprokinetic agent with a lack of serious adverse reactions, unlike some other agents that have a risk of drug-induced QT interval prolongation. It is well known that ␣ 2 -adrenergic agents such as clonidine depress gastrointestinal motor function via the inhibition of ACh release from cholinergic nerve terminals and consequently delay gastric emptying and intestinal transit (Taylor and Mir, 1982;Tack and Wood, 1992;Colucci et al, 1998). Our present study indicated that, like cisapride, acotiamide improved clonidine-induced gastric hypomotility in dogs.…”
Section: Gastroprokinetic Activity Of Acotiamide In Dogs 797supporting
confidence: 59%
“…These results suggest that acotiamide may be a new orally active gastroprokinetic agent with a lack of serious adverse reactions, unlike some other agents that have a risk of drug-induced QT interval prolongation. It is well known that ␣ 2 -adrenergic agents such as clonidine depress gastrointestinal motor function via the inhibition of ACh release from cholinergic nerve terminals and consequently delay gastric emptying and intestinal transit (Taylor and Mir, 1982;Tack and Wood, 1992;Colucci et al, 1998). Our present study indicated that, like cisapride, acotiamide improved clonidine-induced gastric hypomotility in dogs.…”
Section: Gastroprokinetic Activity Of Acotiamide In Dogs 797supporting
confidence: 59%
“…10,11 IBs modulated cholinergic motor function in guinea-pig ileum through an interaction with presynaptic a2D-adrenergic receptors. 12 This assumption was corroborated considering that the involvement of presynaptic imidazoline receptors in cholinergic motility of guinea pig ileum was excluded. 12 In addition, the involvement of a1-ARs in mediating relaxation of the carbachol-evoked contraction in rat ileum longitudinal muscle has been demonstrated, 13,14 whereas an interaction between a1-adrenergic receptors activation and I2-IBs binding in the same organ has been hypothesized.…”
Section: Introductionmentioning
confidence: 84%
“…21 Clonidine, an adrenergic α2 receptor agonist, is known to induce hypomotility and delayed transit of the stomach and intestine, via the inhibition of acetylcholine release from cholinergic nerve terminals. 22,23 A delayed gastric emptying model induced by α2-adrenoceptor agonists has been used to demonstrate the effect of gastroprokinetic agents in animals. 24,25 In the present study, we showed that the pretreatment of clonidine significantly reduced motility of the gastric antrum, that is keeping with the previous observations.…”
Section: Discussionmentioning
confidence: 99%